Distinct patterning responses of wing and leg neuromuscular systems to different preaxial polydactylies - Luxey, Maëva; Stieger, Gabriela; Berki, Bianka; Tschopp, Patrick (Frontiers in Cell and Developmental Biology, 2023)
The tetrapod limb has long served as a paradigm to study vertebrate pattern formation and evolutionary diversification. The distal part of the limb, the so-called autopod, is of particular interest in this regard, given the numerous modifications in both its morphology and behavioral motor output. While the underlying alterations in skeletal form have received considerable attention, much less is known about the accompanying changes in the neuromuscular system. However, modifications in the skeleton need to be properly integrated with both muscle and nerve patterns, to result in a fully functional limb. This task is further complicated by the distinct embryonic origins of the three main tissue types involved – skeleton, muscles and nerves – and, accordingly, how they are patterned and connected with one another during development. To evaluate the degree of regulative crosstalk in this complex limb patterning process, here we analyze the developing limb neuromuscular system of Silkie breed chicken. These animals display a preaxial polydactyly, due to a polymorphism in the limb regulatory region of the Sonic Hedgehog gene. Using lightsheet microscopy and 3D-reconstructions, we investigate the neuromuscular patterns of extra digits in Silkie wings and legs, and compare our results to Retinoic Acid-induced polydactylies. Contrary to previous findings, Silkie autopod muscle patterns do not adjust to alterations in the underlying skeletal topology, while nerves show partial responsiveness. We discuss the implications of tissue-specific sensitivities to global limb patterning cues for our understanding of the evolution of novel forms and functions in the distal tetrapod limb.